Impacto da fibrilhação auricular nas síndromes coronárias agudas - Torres, M; Rocha, S; Marques, J; Nabais, S; Rebelo, A; Álvares-Pereira, M; Azevedo, P; Correia, A (Sociedade Portuguesa de Cardiologia, 2008)
INTRODUCTION: Atrial fibrillation (AF) is a relatively common arrhythmia in the context of acute coronary syndromes (ACS). However, the impact of AF on these patients' survival is not well established. The present study aimed to estimate the prevalence of AF in ACS patients and to evaluate its impact on in-hospital and six-month post-event mortality, from any cause. METHODS: This was a retrospective cohort study that included 1183 patients admitted consecutively to a Coronary Care Unit with ACS. Demographic and clinical data and information from various complementary exams were collected and occurrence of AF during the first 48 hours of hospitalization was analyzed. Six-month follow-up was achieved in 95.9% of the patients. Logistic regression statistical analysis was used to identify independent predictors of in-hospital and six-month post-event mortality. RESULTS: AF was diagnosed in 140 patients (11.8%); these patients were older (73.89 +/- 8.69 vs. 63.20 +/- 12.73 years; p<0.0001) and less likely to be male (60.0% vs. 74.1%; p=0.001), and had a lower prevalence of dyslipidemia (32.9% vs. 44.1%; p=0.001) and smoking (10.0% vs. 25.9%; p<0.0001). Fewer patients with AF underwent reperfusion therapy (19.3% vs. 29.7%; p=0.006), beta-blocker therapy (72.1% vs. 85.7%; p<0.0001), and cardiac catheterization (48.2% vs. 62.9%; p=0.001) or percutaneous coronary intervention (14.3% vs. 23.4%; p=0.01). These patients more frequently developed heart failure (54.3% vs. 28.5%; p<0.0001) and more often presented left ventricular dysfunction (69.3% vs. 57.2%; p=0.002). In patients presenting AF, there were significant increases in in-hospital (12.1% vs. 4.2%; p<0.0001) and six-month mortality (27.2% vs. 8.2%. p<0.0001). In multivariate analysis, AF remained an independent marker of in-hospital (OR 1.95; 95% CI 1.03-3.69; p=0.03) and six-month mortality (OR 2.89; 95% CI 1.67-5.00; p=0.0001), as was age >75 years, severe left ventricular dysfunction and heart failure. The performance of coronary angiography correlated with improved prognosis. CONCLUSIONS: AF in the context of ACS is an independent predictor of increased in-hospital and six-month mortality. These findings should be taken into consideration in the management and treatment of such patients.
Impact of atrial fibrillation in acute coronary syndrome
Keywords: Fibrilhação Auricular; Síndrome Coronária Aguda